PERKEMBANGAN KOPERASI DI INDONESIA SEBAGAI IMPLEMENTASI EKONOMI PANCASILA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
Pancasila is the basis of the state as well as the guideline for the life of the Indonesian people whose moral values are taken from the ancestral culture of the Indonesian nation. Pancasila is also implemented in the economic sector initiated by Mohammad Hatta, namely Pancasila economy. This economic system is based on the values of Pancasila and the 1945 Constitution (UUD 1945) to increase welfare. Cooperatives are a form of implementation of the Pancasila economy in Indonesia which has been growing in the past. Cooperatives in Indonesia are constantly experiencing developments, challenges, and competition with other business entities. This study aims to determine the development of cooperatives in Indonesia with a literature review method with a qualitative approach. Based on the research results, cooperatives in Indonesia are quite good and need development efforts to be more optimal.